Animal Models in Studies of Cardiotoxicity Side Effects from Antiblastic Drugs in Patients and Occupational Exposed Workers. (19th February 2014) - Lamberti, Monica; Giovane, Giancarlo; Garzillo, Elpidio M.; Avino, Franca; Feola, Antonia; Porto, Stefania; Tombolini, Vincenzo; Di Domenico, Marina
Abstract : Cardiotoxicity is an important side effect of cytotoxic drugs and may be a risk factor of long-term morbidity for both patients during therapy and also for staff exposed during the phases of manipulation of antiblastic drugs. The mechanism of cardiotoxicity studied in vitro and in vivo essentially concerns the formation of free radicals leading to oxidative stress, with apoptosis of cardiac cells or immunologic reactions, but other mechanisms may play a role in antiblastic-induced cardiotoxicity. Actually, some new cytotoxic drugs like trastuzumab and cyclopentenyl cytosine show cardiotoxic effects. In this report we discuss the different mechanisms of cardiotoxicity induced by antiblastic drugs assessed using animal models.